2009
DOI: 10.1105/tpc.109.071506
|View full text |Cite
|
Sign up to set email alerts
|

PLAZA: A Comparative Genomics Resource to Study Gene and Genome Evolution in Plants

Abstract: The number of sequenced genomes of representatives within the green lineage is rapidly increasing. Consequently, comparative sequence analysis has significantly altered our view on the complexity of genome organization, gene function, and regulatory pathways. To explore all this genome information, a centralized infrastructure is required where all data generated by different sequencing initiatives is integrated and combined with advanced methods for data mining. Here, we describe PLAZA, an online platform for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
243
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 254 publications
(245 citation statements)
references
References 71 publications
1
243
0
1
Order By: Relevance
“…The study of core plant genes combined with expression states provides a simple means to enlarge our understanding of the evolution of gene function versus regulation. From the 8,478 conserved Arabidopsis core genes (with homologs in all nine plant species present in the PLAZA comparative genomics platform; Proost et al, 2009), 1,787 genes were present in 1:1 orthologous families. Of these core genes, 80% (1,426 of 1,787) had conserved ECC patterns, revealing a 3% increase in conserved coexpression state compared with the average level in the complete data set (P , 8.5e-05; hypergeometric distribution).…”
Section: Ecc Patterns For Evolutionarily Conserved Plant Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of core plant genes combined with expression states provides a simple means to enlarge our understanding of the evolution of gene function versus regulation. From the 8,478 conserved Arabidopsis core genes (with homologs in all nine plant species present in the PLAZA comparative genomics platform; Proost et al, 2009), 1,787 genes were present in 1:1 orthologous families. Of these core genes, 80% (1,426 of 1,787) had conserved ECC patterns, revealing a 3% increase in conserved coexpression state compared with the average level in the complete data set (P , 8.5e-05; hypergeometric distribution).…”
Section: Ecc Patterns For Evolutionarily Conserved Plant Genesmentioning
confidence: 99%
“…Inparalogs are gene duplicates postdating speciation. Recent benchmark studies have shown that the OrthoMCL gene-clustering method performs well in modeling recent and ancient duplication events compared with more advanced methods based on phylogenetic inference Proost et al, 2009). For every functional category (see below), all genes with one or more orthologous gene in the other species were retained for the EC analysis.…”
Section: Identification Of Orthologous Gene Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes orthologous to LNP1 and LNP2 in other species within the land plant lineage (Embryophyta) and containing the InterPro LNP domain (IPR019273) were identified using the P laza 4.0 online platform (Proost et al ., 2009). This resulted in the identification of 87 LNP‐like genes from 49 plant species.…”
Section: Methodsmentioning
confidence: 99%